2011
DOI: 10.1007/s12098-011-0432-y
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Irregularity and Poly Cystic Ovarian Syndrome among Adolescent Girls—A 2 Year Follow-up Study

Abstract: The results of this study support screening for menstrual irregularity, obesity and signs of clinical hyperandrogenism for early diagnosis of PCOS in an effort to improve the reproductive health of adolescent girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 18 publications
0
42
0
1
Order By: Relevance
“…While menstrual irregularity is common, its persistence after 2 years after menarche is associated with PCOS. Nair et al 51 studied a cohort of 136 adolescent girls with confirmed menstrual irregularity; at 2 year follow-up, 51.5% continued to have menstrual irregularity and 36% were diagnosed with PCOS using the Rotterdam criteria. In their cohort, Roe et al 70 found that 98% of adolescents diagnosed with PCOS by the AE-PCOS criteria presented with menstrual irregularity—68.3% with oligomenorrhea, 27.7% with secondary amenorrhea, and 4% with primary amenorrhea.…”
Section: Menstrual Irregularitymentioning
confidence: 99%
“…While menstrual irregularity is common, its persistence after 2 years after menarche is associated with PCOS. Nair et al 51 studied a cohort of 136 adolescent girls with confirmed menstrual irregularity; at 2 year follow-up, 51.5% continued to have menstrual irregularity and 36% were diagnosed with PCOS using the Rotterdam criteria. In their cohort, Roe et al 70 found that 98% of adolescents diagnosed with PCOS by the AE-PCOS criteria presented with menstrual irregularity—68.3% with oligomenorrhea, 27.7% with secondary amenorrhea, and 4% with primary amenorrhea.…”
Section: Menstrual Irregularitymentioning
confidence: 99%
“…Additionally, the reproductive capacity of adolescents also undergoes non-pathological changes during pubertal development that are influenced by the secretion of gonadotropins. These changes are expressed by irregular menstrual patterns and PCOM on ultrasonography, and may even persist for 2 years after menarche [2,15,16,17]. Because all three sets of criteria include abnormal ovulatory patterns and PCOM, the diagnosis in adolescence remains challenging.…”
Section: Pcos In Adolescentsmentioning
confidence: 99%
“…Lately, however, at least some cases of PCOS have been regarded as a disorder of metabolic origin that impairs reproductive function [5]. Since obesity, particularly in the abdominal region, is found in ∼50% [9,29] of women with PCOS, and because obesity appears in mid-childhood and increases during puberty [6,16,27], excess adiposity has generated a great deal of attention. Furthermore, the clinical phenotype and the development of PCOS are thought to be reinforced by obesity [2,7,27,30], especially among those who are genetically prone to the disorder [7].…”
Section: Biological Originmentioning
confidence: 99%
“…Most prevalence studies in India are in hospital set-ups and recently a few studies among adolescents in schools report prevalence of PCOS as 9.13% to 36%. [1415] It is appropriately pointed by Gainie and Kalra[16] that the health budget of India is unlikely to meet the costs posed to tackling the associated multiple consequences of PCOS. It is time that this warning is heeded and at national level the disease is recognized as an important noncommunicable disease.…”
Section: Introductionmentioning
confidence: 99%